Decreasing Population and Rising Costs of Providing Water and Sewage Treatment within Cities: A Case Study - Peter Haug (European Regional Science Association (ERSA), 2004)
The paper investigates empirically how costs per inhabitant depend on population density, considering public water and sewerage industry as example. Diverging from prior work, spatial differences in distribution costs within a German municipality are calculated for both industries by using appropriate cost accounting data. Choosing suitable cost allocation bases turned out to be the main problem. The results provide some evidence of the assumed u-shaped per-capita cost curve only for the distribution of water, whereas per-capita distribution costs of the sewerage industry tend to decrease steadily with rising population density. Thus, cost-cover percentages of water and sewage charges rise with increasing population density. These findings suggest firstly, to take rising per-capita costs of providing network-related goods and services into consideration for city deconstruction programmes (e.g. “Stadtumbau Ost”) and secondly, to differentiate charges for local public goods spatially according to the real costs. JEL classification: R00, L32, L95, H42
Keywords: R00; L32; L95; H42; 330